2019
DOI: 10.1155/2019/4578327
|View full text |Cite
|
Sign up to set email alerts
|

Serum Uric Acid Is Independently Associated with Risk of Obstructive Sleep Apnea-Hypopnea Syndrome in Chinese Patients with Type 2 Diabetes

Abstract: Purpose. We aimed to investigate the association between serum uric acid (SUA) levels and obstructive sleep apnea-hypopnea syndrome (OSAHS) in patients with type 2 diabetes. Methods. A cross-sectional study of 212 type 2 diabetes mellitus (T2DM) patients was conducted in Xiamen, China. All patients underwent polysomnography (PSG) recordings for OSAHS diagnosis. Patients were grouped according to the apnea-hypopnea index (AHI) as mild (5-14.9), moderate (15-29.9), and severe (≧30) OSAHS. Patients with AHI≤4.9 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 30 publications
3
17
0
Order By: Relevance
“…In addition, our study showed that serum uric acid expression was significantly higher in the OSA&non-T2D group than in the control group, which was in accord with the previous research [ 29 , 30 ]. Meanwhile, serum uric acid levels were significantly reduced after OSA treatment with continuous positive airway pressure or weight reduction [ 31 ].…”
Section: Resultssupporting
confidence: 92%
“…In addition, our study showed that serum uric acid expression was significantly higher in the OSA&non-T2D group than in the control group, which was in accord with the previous research [ 29 , 30 ]. Meanwhile, serum uric acid levels were significantly reduced after OSA treatment with continuous positive airway pressure or weight reduction [ 31 ].…”
Section: Resultssupporting
confidence: 92%
“…An observational study conducted in T2DM patients found that the prevalence rate of OSAS was 86%, of which the moderate and severe OSAS were 30.5% and 22.6%, respectively [ 7 ]. Our previous study also found 80.3% of T2DM patients had OSAS which was consistent with others [ 8 ]. A community-based study indicated that OSAS was independently related to the development of insulin resistance and could promote the occurrence of T2DM [ 9 ].…”
Section: Introductionsupporting
confidence: 92%
“…They reported an increase in SUA of 0.3 mg/dL and gout odds ratio of 2.24 for each increase in genetically predicted BMI of 4.6 kg/m 2 [ 23 ]. Another factor that has shown an association with higher SUA is obstructive sleep apnea–hypopnea syndrome (OSAHS) [ 24 ]; however, meta-analyses have not revealed an effect of using continuous positive airway pressure (CPAP) in OSAHS on SUA levels [ 25 ].…”
Section: Treatment Options For Hyperuricemiamentioning
confidence: 99%